АХБОРОТ МАДАНИЯТИ ТУШУНЧАСИ ВА УНИНГ ПЕДАГОГИК ТАЛҚИНИ - Хужаниёзова, З.О. (SCIENCE and SOCIETY, 2018)
The article deals with the notions «information», «information culture». The author of the article describes the work with information and states about the necessity of forming information culture.